2017
DOI: 10.1007/s12022-017-9468-5
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Teratoma: a Case Series and Review of the Literature

Abstract: Adrenal teratomas are rare neoplasms and there is limited data on their surgical outcomes and long-term prognosis. We aimed to review our institutional experience and compare this to the existing literature on adrenal teratomas in adults and children. An institutional pathology database was searched for cases of adrenal teratoma (June 1956-July 2016). Clinical and imaging data were abstracted from the medical records and pathology slides were obtained for review. In addition, a PubMed search for "adrenal terat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Pediatric adrenal teratomas are uncommon, repre-senting~5% of all pediatric teratomas (12). Although pediatric cases of adrenal teratomas have not been found in our literature review, primary adrenal teratomas have been reported in neonates, infants and children.…”
Section: Discussionmentioning
confidence: 70%
“…Pediatric adrenal teratomas are uncommon, repre-senting~5% of all pediatric teratomas (12). Although pediatric cases of adrenal teratomas have not been found in our literature review, primary adrenal teratomas have been reported in neonates, infants and children.…”
Section: Discussionmentioning
confidence: 70%
“…Till now the maximum size reported in literature is of mature cystic teratoma in a 33 yr old lady, extending from pancreas upto pelvis about 35x35cm size (weight not mentioned) and of 22x17x7cm size and 1.6kg weight, in a 39 yr old lady, at rt adrenal region. 5,8 Considering volume-33,750cm 3 , weight 12kg vs age of patient the case is probably largest ever reported in a child as young as 15 yrs of age. There was 10kg fluid and 2kg solid mass in tumor ( Figure 5).…”
Section: Discussionmentioning
confidence: 92%
“…There are report of adrenal origin of mature teratoma. 3,4 Most of benign teratomas are asymptomatic and attain enormous size before presentation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations